PENGARUH PENDEKATAN CTL TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR - Nuryanto, Ridho; Kresnadi, Hery; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the effect of contextual teaching and learning approach on science learning outcomes of 4th grade students of Pontianak Kota 66 public elementary school. This research use experimental method with a quasi experimental form and nonequivalent control group design. The population of this study is all 4th grade students of Pontianak Kota 66 public elementary school totaling 65 students. The sampling technique uses nonprobability sampling with purposive sampling type. Data collection techniques use direct observation and measurement techniques. The research instrument used was a written test with multiple choice form. Based on data analysis result, average score post-test in the experimental class and the control class were 66,333 and 56,774. Result of t-test obtained tcount = 2,538 and ttable = 2,001 (? = 5%; db = 59). Because tcount (2,538) > ttable (2,001), its mean Ha accepted and H0 rejected. The effect size result is 0,638 with medium criteria. The conclusion in this study is that there is the effect the effect of contextual teaching and learning approach on science learning outcomes of 4th grade students of Pontianak Kota 66 public elementary school with medium criteria. Keyword : The Effect, Contextual Teaching and Learning Approach, Learning Outcomes, Natural Science